AN EPIDEMIOLOGICAL STUDY OF DIETARY AND EXERCISE HABITS AS CO-RELATES OF HYPERTENSION IN PERSON AGED 45 AND ABOVE IN AGRA DISTRICT - Agrawal, Renu; Chaturvedi, Mridul; Singh, Sujan; Gupta, Subhash Chandra (Indian Journal of Community Health, 2012)
Background: Due to changing lifestyle in Indian population prevalence of hypertension is increasing which needs modification in dietary and exercise habit of the general population. Objective: A study was designed to correlate dietary and exercise habits with hypertension in general population. Material and methods: Present study is a community based cross sectional study among persons aged more than 45 years in Agra district using PPS multi stage simple random sampling technique with a sample size of 553, which includes 260 persons from urban and 293 persons from rural area. Results: Out of 544 persons studied, overall prevalence of hypertension was found to be 36.21% which was 41.47% in urban and 31.47% in rural areas. Prevalence decreases significantly in person engaged in heavy physical activity (14.54%). Hypertension is more prevalent in non vegetarian diet (44.26%) as compared to vegetarian (33.88%) and very high in population consuming extra salt (73.77%). Conclusion: Prevalence of hypertension in this study is 36.21% and increases with lack of exercise and yoga, non vegetarian diet and consumption of extra salt in diet.